PENDIDIKAN ANTI KORUPSI: KONSEP PENDIDIKAN KARAKTER DAN TANTANGANNYA - Nurudin, Nurudin; Nur Fauzi, M. Asif; Barory, Chulil (Educatus, 2024)
This research is motivated by the high number of acts of corruption in Indonesia currently and it is deemed necessary to implement anti-corruption education in schools as a preventive measure from an early age. Anti-corruption education in schools is a strategic effort to shape students' character with integrity and responsibility. This educational concept not only emphasizes understanding corruption as a social problem, but also on developing strong moral values ​​in forming honest and transparent attitudes and behavior. This research uses a qualitative descriptive method with interview, observation and documentation data collection methods. The data analysis used was through data triangulation and continued with drawing conclusions. This research explores the concept of character education in the context of anti-corruption education and the challenges faced in its implementation in the educational environment. These challenges include limited resources, lack of understanding and awareness of the importance of anti-corruption education, as well as resistance to cultural change that supports integrity. To overcome these challenges, this research suggests a collaborative approach between schools, anti-corruption institutions and communities to increase understanding and commitment towards anti-corruption education. Proposed strategies include developing inclusive curricula, ongoing training for teachers, and building a school culture that encourages honesty and accountability.